Hitmen: the mafia, drugs, and the East Harlem Purple Gang - Deitche, Scott M. (Rowman & Littlefield, 2022)
Origins -- What's in a name? -- A capacity for violence -- The drug game -- Rockland County -- The Milgram murder -- .22 caliber killers -- The shopping spree -- The viserto drug trial -- The early eighties -- A killing on thunderboat row -- The crackdown -- The Michael Meldish murder -- The leaders of the families.